The Study of Stability and Combustion Characteristics O Water In Diesel Emulsion Fuel - Syafiq, Zulkifli; O., Fahmi; Awad, Omar I.; Abdul Adam, Abdullah (2016)
A single cylinder diesel engine study of water in diesel emulsions was conducted to investigate the stability effect of emulsion fuel on three different fuel blends and the water emulsification effect on the engine performance. Emulsified fuels contained 2% of surfactant including Span 80 Tween 80 and tested 10 HLB number. The blends also varied of 5%, 10% and 15% of water in diesel ratios namely as BSW5, BSW10 and BSW15. The fuel blends performance was tested using a single cylinder, direct injection diesel engine, operating at 1860 rpm. The results on stability reveal that device high shear homogenizer yields the good emulsion stability than mechanical stirrer and ultrasonic water bath. Furthermore, the results on performance show that the ignition delay and peak pressure increase as the water percentage increase. The results indicate the addition of water in form of emulsion produced a significant decrease in engine power.